Pemberian Tepung Brangkasan Ubi Jalar Terfermentasi Terhadap Komposisi Fisik Karkas Ayam Kampung Super Umur 10 Minggu - Yudisthira, Putu; I Gusti Agus Maha Putra Sanjaya; Ni Ketut Etty Suwitari (Gema Agro, 2023)
Abstract The livestock sector plays a real role in national food security through the supply of animal protein, one of which is super village chickens. In increasing the productivity of livestock the most important is rations. Feed materials that need to be used as alternative feed materials include agricultural waste, one of which is sweet potato brangkasan (Ipomoea batatas). The purpose of this study was to find out the effect of giving sweet potato brangkasan flour to the variable physical composition of chicken villages until the age of 10 weeks. The experimental design used is a Complete RandomIzed Design (RAL) consisting of 5 treatments, namely: R0 (Ration without sweet potato brangkasan flour as a control), R1 (Ration contains 3% sweet potato brangkasan flour without fermentation), R2 (Rations contains 3% fermented sweet potato brangkasan flour), R3 (Ransum contains 6% fermented sweet potato brangkasan flour), R4 (Ration contains 9% fermented sweet potato brangkasan flour). Each treatment is repeated three times. The results showed that the addition of fermented and non-fermented sweet potato brangkasan flour did not have a noticeable effect (P>0.05) on the physical composition of the thigh carcass and the physical composition of the meat as well as on the skin and subcutaneous fat of the chicken breast super village, but a real effect (P<0.05) on the physical composition of the breastbone. The provision of 3% fermented sweet potato flour (R2) tends to be able to give the results of the physical composition of the chest and thigh carcass higher. Keywords: Super Kampung Chicken, Carcass Physical Composition, Sweet Potato Flour